1981
DOI: 10.1530/jrf.0.0610025
|View full text |Cite
|
Sign up to set email alerts
|

A glycolytic product is obligatory for initiation of the sperm acrosome reaction and whiplash motility required for fertilization in the mouse

Abstract: The substrate requirements for capacitation of epididymal mouse spermatozoa, initiation of the acrosome reaction and support of fertilization of mouse eggs in vitro were examined by assessing not only fertilization rates, but also the stages of egg activation and sperm head decondensation in fertilized eggs to monitor the temporal aspects of these processes. Although early events of capacitation did not require exogenous substrates, the fertilization process was effectively blocked at the terminal stages of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
4

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(164 citation statements)
references
References 16 publications
13
147
4
Order By: Relevance
“…It would therefore appear that the introduction of albumin triggers the acrosome reaction in those cells that otherwise would have lost the acrosome during the incubation phase. A similar response was noted when glucose was introduced to suspensions capacitated in glucose-free medium (Fraser & Quinn, 1981). Whether the fertilizing spermatozoa are drawn from this pool, however, or from the acrosome-intact cells with the potential to undergo the acrosome reaction is unclear.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It would therefore appear that the introduction of albumin triggers the acrosome reaction in those cells that otherwise would have lost the acrosome during the incubation phase. A similar response was noted when glucose was introduced to suspensions capacitated in glucose-free medium (Fraser & Quinn, 1981). Whether the fertilizing spermatozoa are drawn from this pool, however, or from the acrosome-intact cells with the potential to undergo the acrosome reaction is unclear.…”
Section: Discussionmentioning
confidence: 66%
“…After preincubation for 30 or 120 min, aliquants of sperm suspensions were diluted 10-fold, incubated for 5 min and then subjected to filtration on short columns prepared in Pasteur pipettes (Fraser & Quinn, 1981 ) to select motile, potentially fertilizing spermatozoa for assessment. Preliminary studies indicated that a macromolecular component (PVA) in the medium and a column made of Sephadex G-25 (Fraser & Quinn, 1981), rather than glass beads (Fraser, 1983b), prevented excessive sticking of cells during filtration which might distort the results. This problem does not arise when BSA is included in the medium.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, hyperactivated motility may help the sperm to penetrate the egg vestments (Suarez et al 1991;Stauss et al 1995;Ho and Suarez 2001). In rodents, and probably in other species, hyperactivated sperm motility is also correlated with the ability of a sperm to fertilise an oocyte in vitro (Fraser and Quinn 1981;Boatman and Robbins 1991). Thus, the bulk of evidence suggests that a normal sperm must be able to acquire both activated motility in the caudal female reproductive tract and uterus and hyperactivated motility in the oviduct for it to have a reasonable chance of fertilising the egg.…”
Section: Two Types Of Physiological Mammalian Sperm Motilitymentioning
confidence: 99%
“…It has also been shown that mammalian sperm produce lactate from glucose under aerobic conditions (Storey and Kayne 1975). Adenosine triphosphate production through glycolysis is required for hyperactivated sperm motility (Hoshi et al 1991;Urner and Sakkas 1996) and inhibition of oxidative phosphorylation does not block fertilisation (Fraser and Quinn 1981).…”
Section: Fuel Support and More: The Fibrous Sheathmentioning
confidence: 99%
“…Spermatozoa were incubated under conditions which support capacitation (Fraser, 1983) and modified conditions which compromise expression of fertilizing ability (Fraser & Quinn, 1981;Fraser, 1982Fraser, , 1983Fraser, , 1987. The standard incubation medium supports capacitation, which is generally complete within 120 min.…”
Section: Introductionmentioning
confidence: 99%